Social Support Associated with Quality of Life in Home Care Patients with Intractable Neurological Disease in Japan - Tomoko Nishida; Eriko Ando; Hisataka Sakakibara (Nursing Research and Practice)
The aim of the present study was to investigate what kinds of social supports contribute to the higher quality of life (QOL) of home care patients with intractable neurological disease. We investigated the World Health Organization Quality of Life-BREF (WHOQOL-BREF) and social supports to 74 patients with intractable neurological disease in a city of the Aichi prefecture, Japan. Association between WHOQOL and social supports was examined using multiple logistic regression analyses adjusting activities of daily living (ADL). High WHOQOL scores were associated with “attending patient gatherings held by the public health center,” “having someone who will listen empathically to anxieties or troubles,” and ADL. Physical health was associated with ADL, while psychological well-being was related to “having a hobby,” “having someone who will listen,” and “having a hospital for admission in emergencies.” Patients not having someone who will listen were more likely to participate in the gatherings. The present findings suggest that having someone who will provide emotional support is important for home care patients with neurological diseases. Patient gatherings held by the public health center were expected to provide patients with emotional support.